Please do your best to explain since I want to learn how to do this as well.

CPhilFanboy Apr 16, 2021

#1**+1 **

(b):

Take a point (a,b) on the graph of y=f(x), so b=f(a). Since \(\left( 3a - 1, \frac{b}{2} \right)\) lies on the graph of y=g(x) we have that \(\frac{b}{2} = g(3a - 1). \)

Substituting b=f(a) we get \(\frac{f(a)}{2} = g(3a - 1).\)

In order to express g(x) in terms of f(x) we can let x = 3a-1 Then a=\(\frac{x + 1}{3}\), so

\(g(x) = \frac{f(a)}{2} = \frac{1}{2} f \left( \frac{x + 1}{3} \right).\)

Mathdory Apr 16, 2021

#2**+1 **

Sorry that I can't do the problems (a) and (c) because the LaTeX code is too complicated for drawing the diagram. I hope you understand

Mathdory Apr 16, 2021

#3

#4**+1 **

This link might help a bit

https://web2.0calc.com/questions/help-pls-due-today-help-needed-asap

Mathdory
Apr 16, 2021

#5**+1 **

Yeah... I looked at that one, I wasn't able to understand what they are saying though, thanks for the help!

CPhilFanboy
Apr 16, 2021

#7**+2 **

First, we observe that the graph of y=f(x) consists of line segments, connecting the points (-4, 4), (-1,0), (0,2), and (4,-4).

So to plot the graph of y=g(x) we can apply the transformation \((a,b) \to \left( 3a - 1, \frac{b}{2} \right)\) to each of these points, and then connect them. This gives us the points (-13,2), (-4,0), (-1,1), and (11,-2).

Hope this helps!

I got it working.

Mathdory Apr 16, 2021